answersLogoWhite

0


Best Answer

3y + 8 = 3

-8 -8

3y=-5

(3y)/3=-5/3

y=(-5/3)

User Avatar

Wiki User

โˆ™ 2010-03-17 14:31:52
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

Multiplication chart! :)

12 cards

2x1

2x2

2x3

2x4

โžก๏ธ
See all cards

Math and Arithmetic

20 cards

The length of a rectangular floor is 2 feet more than its width The area of the floor is 168 square feet Kim wants to use a rug in the middle of the room and leave a 2 foot border of the floor visib

The perimeter of a rectangle is 18 feet and the area of the rectangle is 20 square feet what is the width of the rectangle

The sum of two numbers is 19 and their product is 78 What is the larger number

A rectangular garden has a perimeter of 48 cm and an area of 140 sq cm What is the width of this garden

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: How do you solve 3y plus 8 equals 3?
Write your answer...
Submit
Related questions

How do you solve 7x plus 3y equals 30 -2x plus 3y equals 3 in an order pair?

(3,3)


Can You Solve 2x plus 3y equals 18 and 2x-3y equals -6 Using The Elimination Method?

Yes and it works out that x = 3 and y = 4


How do you solve -3y plus x equals 7?

Divide all terms by -3 then it will be in slope intercept form


How do I solve 4x plus 3y equals 7 whenyour looking for slope intercept?

4x + 3y = 7 y = [(-4)/3] x + 7/3


5x plus 3y plus z equals -29 solve this system of equation?

To solve an equation with three unknowns, x, y and z, you require 3 independent equations.


How do you solve 2x-y equals -6 and 2x plus 3y equals 9?

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9


3y equals ab solve for variable y?

3y=ab. Divide by 3 to get y=ab/3


Can anyone help solve this problem 7y plus 2 equals 3y-10?

7y = 3y - 12 4y = -12 y = -3


Find the answers in 4x plus 3y equals 12 7x plus 3y equals 21?

x = 3 and y = 0


What is the solution of x plus y equals -2 and 2x plus 3y equals -9?

x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5


-3 plus 3y equals 2y plus 5?

3y - 3 = 2y + 5 3y - 2y = 5 + 3 y = 8


Solve the system of equations enter your answer as an ordered pair 6x - y equals 33 6x plus 3y equals 45?

It works out that x = 6 and y = 3 or as (6, 3)


5x plus 3y equals 13 as a ordered pair?

If 5x plus 3y equals 13, the x equals 2 and y equals 1. This is because 5x2=10 and 3x1=3, and 10+3=13.


2y plus 3 equals 3y plus 9?

2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6


What is the common point of these equations 2x plus 3y equals 12m and x - 3y equals -3?

It is [4m-1, (4m-2)/3]


Solve 2x plus 3y equals 12 when x equals 1.45?

2x + 3y = 12 x = 1.45, so 2 * 1.45 + 3y = 12 2.9 + 3y = 12 3y = 12 - 2.9 = 9.1 y = 9.1/3 = 3.0333... or 91/30 or 3 1/30.


How can you solve this elimination x plus 8y equals 3 2x plus 3y equals -7?

x + 8y = 3 therefore 2x + 16y = 6 (a) 2x + 3y = -7 (b) Subtract (b) from (a): 13y = 13 so y = 1 and x = -5


What is the common point of these equations 2x plus 3y equals 12 and x - 3y equals -3?

(3, 2) because x = 3 and y = 2


3x plus 2y equals -3 2x plus 3y equals -2?

(-1, 0)


What is 2y plus 2 equals 3y plus 3?

y = -1


4xplus5 equals 3y plus 2 than y equals?

4x+3/3=y


How do you solve each system by substitution or addition 2y-x equals 3 and x equals 3y-5?

Add the two equations together. The x disappears. 2y - x = 3 + x = 3y - 5 ------------------------ 2y = 3y -2 Can you finish it from there?


How do you solve 3y 5 equals 11?

n=3,y=4 2(n+3y)=30


Solve the system using any algebraic method a. -5x-y equals -3 ---- x-4y equals 9 b. x plus y-z equals 7 ---- 2x-3y plus z equals 2 ---- 4x plus 2y-2z equals 20?

y=5x+2 if y equals -4


How do you solve this problem it just says solve x2 plus 3y equals 7 3x plus y2 equals 3?

x2 + 3y = 7 3x + y2 = 3 3y = x2 + 7 y2 = -3x + 3 y = x2/3 + 7/3 y = ± √(-3x + 3) If you draw the graphs of y = x2/3 + 7/3 and y = ± √(-3x + 3) in a graphing calculator, you will see that they don't intersect, so that the system of the given equations has not a solution.